Insights into liquid phase sintering mechanism of high-alumina and low-silica hematite ores - Wanlong Fan; Zhiwei Peng; Tuo Pan; Huibo Liu; Shaochang Nie; Lin Xiong; Qiang Zhong; Mingjun Rao (Minerals Engineering, 2026)

From overhead to human eye level: reassessing urban green spaces equity across socioeconomic gradients through multi-perspective visionscape analysis - Yufei Rao; Yashi Wu; Yao Qian; Lin Wang; Zhibang Xu; Guofan Shao; Lina Tang (Sustainable Cities and Society, 2026)

Structure-dependent modulation of Morchella esculenta protein by ferulic and chlorogenic acids: Improving techno-functionality and digestibility of a fungal alternative protein - Ying He; Zhenan Rao; Ziang Tian; Xiaojuan Lei; Jichun Zhao; Lin Lei; Jian Ming (Food Research International, 2026)

Engineering a uridine diphosphate galactosyltransferase PhUGT enables efficient whole-cell biosynthesis of hyperoside from quercetin - Mengjiao Li; Zhiwei Deng; Yu Geng; Lu Cai; Shan Lin; Yue Gao; Yijian Rao (Food Bioscience, 2026)

Fabrication of algal oil oleogels with zein-alginate Conjugates: Ca2+-tuned foam templating - Yuge Bao; Qiming Wang; Zhenan Rao; Yangjie Zhou; Jichun Zhao; Lin Lei; Jian Ming (Food Hydrocolloids, 2026)

Density functional theory-assisted: In-situ growth of NH2-UiO-66 on polypyrrole for high-selectivity electrochemical detection of nitrophenol isomers - Xuemei Wang; Rao Peng; Lin Fan; Yi Song; Shujie Wang; Xinzhen Du; Xiaoquan Lu (Analytica Chimica Acta, 2026)

ROS-responsive “Trojan Horse” nanoplatform via homotypic fibroblast-membrane camouflage for precision reprogramming of pathogenic synoviocytes in rheumatoid arthritis - Hua-Zhong Ying; Zhen-Hua Ying; Zhi-Min Rao; Song-Lin Jiang; Song-Zhao Zhang; Ying-Jun Lou; Karim Malik; Arman Chowdhury; Chen-Huan Yu (Chemical Engineering Journal, 2026)

Chemical Characteristics, Sources, and Transport Pathways of PM2.5 in a Mid-Altitude Industrial City of the Upper Yellow River Basin - Lin Yi; Juanjuan Qin; Yuanyuan Qin; Yuwei Gao; Jingnan Li; Xiaoying Su; Shuming Zhang; Zhiguo Rao; Jihua Tan; Peng Yi (Water, Air, & Soil Pollution, 2026)

Effect of the thickness of overlying soil on the location of trailing edge cracks in soil–bedrock landslides induced by water softening - Yun-kang Rao; Jia-xin Chang; Hai-ying Fu; Tao Yang; Huai-lin Chen; Zhe Zhang; Yi Yang; Rui Huang (Bulletin of Engineering Geology and the Environment, 2026)

A 13,100-year record of net primary productivity from subtropical China reveals shifting climatic and anthropogenic controls - Lin Zhao; Shanshan Meng; Zijian Liu; Tengwen Long; Zhiguo Rao; Haibin Wu (Anthropocene, 2026)

Can the ozone valley intensity over the Tibetan Plateau influence the East Asian summer rainfall? - Lin Shen; Jian Rao; Yimin Liu; Xiaoqi Zhang; Dong Guo (Climate Dynamics, 2026)

Multiscale molecular engineering of a thermogelling polymer integrating quantum mechanics, polymer chemistry and artificial intelligence - Tao Sun; Weihan Rao; Junyi Li; Lingxi Li; Yiman Wei; Shuquan Cui; Wenqian Li; Yanshuang Zhang; Yixuan Wang; Lin Yu; Jiandong Ding (Science Bulletin, 2026)

Comparative analysis of topsoil and moss pollen traps in central Hunan low mountains: Implications for modern pollen–vegetation calibration in subtropical China - Jingling Wen; Lin Zhao; Huihan Yang; Zhiguo Rao (Review of Palaeobotany and Palynology, 2026)

Low elevation and humid climate in the Eocene Gerze basin, central Tibet: Insights from multi-proxy isotopic analyses - Xiaohui Liu; Yimin Liu; Armelle Ballian; Miguel Bernecker; Jens Fiebig; Ying Rao; Lin Ding; Andreas Mulch (Global and Planetary Change, 2026)

Morphotectonic characteristics of the Xiongpo anticline in the southwestern Sichuan Basin, China: Implications for active folding mechanisms - Xiaohan Yin; Gang Rao; Lin Gao; Yan Wu; Yaqi Zhong; Pengcheng Tang; Renfu Wang (Geomorphology, 2026)

Discovery, molecular docking, and umami-enhancing synergy of five novel umami peptides from Dictyophora rubrovolvata: Insights into T1R1/T1R3 interaction - Jialin Li; Jiaqi Chen; Zhenan Rao; Han Xie; Jichun Zhao; Lin Lei; Kaifang Zeng; Jian Ming (Food Chemistry, 2026)

Regulation of photosynthesis and ROS homeostasis by Fd1 and FNR1 confers thermotolerant yield stability in rice - Qiaoyan Wang; Qingmei Su; Man Li; Dongdong Chen; Yuchun Rao; Pengfei Dong; Bingxin Ye; Tingyi Wang; Zhiqi Hao; Rui Pang; Ruiying Li; Guangheng Zhang; et al. (Science Bulletin, 2026)

Rapid Early Miocene surface uplift of the Yarlung Tsangpo Suture Zone: Constraints from stable and clumped isotopes - Xiaohui Liu; Yimin Liu; Xudong Guo; Suoya Fan; Xiaoyu Guo; Wenxing Hao; Xingfu Huang; Xiaoming Shen; Qiuhua Ren; Ying Rao; Lin Ding; Rui Gao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Ultrastructural response of the retinal cells and neurovascular unit to neuroinflammation induced by lipopolysaccharide - Bilin Rao; Xiaotian Wu; Xiaoqing Liu; Fenglan Wang; Fang He; Xin Lin; Guiyu Guan; Xiaoqian Lai; Jun Zhang (Brain Structure and Function, 2026)

Enhanced human activities disturbed vegetation since 3500 years ago in southern China - Lin Zhao; Zijian Liu; Xiaoxu Qu; Zhongwei Shen; Zhiguo Rao; Xianyong Cao (Science Bulletin, 2026)

Vegetation-hydrology coupling in subtropical China during the Younger Dryas: A quantitative reconstruction from high-resolution pollen records at Luoxiao Mountains - Lin Zhao; Jinlong Liang; Zijian Liu; Tengwen Long; John Dodson; Lidan Liu; Yunxia Li; Zhongwei Shen; Zhiguo Rao; Xiaojian Zhang; Huayu Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Disrupting the lepidolite structure via low-temperature (NH4)2SO4 and Na2SO4 roasting: Achieving efficient co-extraction of lithium, rubidium, and cesium from lepidolite - Shuping Cheng; Zhipeng Rao; Jiezhong Zou; Junfeng Zhang; Guobiao Li; Huiquan Li; Ting Lai; Wanhai Xiao; Yong Lin; Tinggang Li; Dong Wang (Journal of Environmental Chemical Engineering, 2026)

RNAi against ribosomal protein L27 gene impairs larval development in Phthorimaea operculella - Yu Zhang; Zhong-Yuan Wang; Ya-Hao Rao; Juan Peng; Lin Jin; Guo-Qing Li (Journal of Asia-Pacific Entomology, 2026)

Strategies for high-efficiency salt management in solar-driven interfacial evaporation - Jinjing Yang; Jing Zhang; Zhongxing Xu; Lin Ren; Longshi Rao; Junyang Tao; Yifeng Liao; Shudong Yu (Desalination, 2026)

Application of a novel complex surfactant to enhance the bioremediation of weathered-diesel oil contaminated soils: mechanism and mesocosm-scale study - Wei-Ting Chen; Jiun-Hau Ou; Wei-Zhe Lin; Rao Y. Surampalli; Ssu-Ching Chen; Chih-Ming Kao (Journal of Soils and Sediments, 2026)

Dual-phase adhesive secretion in the stalked barnacle Capitulum mitella - Ziquan Zhou; Zewen Zheng; Xiuqin Bai; Xiaozhen Rao; Gang Lin (Biofouling, 2026)

Ambient ozone exposure associated with incidence and accelerated occurrence of cardiometabolic diseases and potential mediating effect of blood pressure: A prospective cohort study based on the GOLD-Health - Zhonghua Ai; Hui Liu; Weiquan Lin; Peng Hu; Qin Zhou; Fei Tian; Manting Rao; Zitong Zhuang; Xiangyi Liu; Shengtao Wei; Aaron M. Qian; Hualiang Lin; et al. (Atmospheric Environment, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Holocene precipitation/humidity change trend in subtropical southern China: Contrary results, analyses and prospective - Xiaoxu Qu; Yunxia Li; Zhongwei Shen; Lin Zhao; Siyu Wu; Zhiguo Rao (Quaternary Science Reviews, 2026)

Opisoma menchikoffi Dubar, 1948: New occurrences from the Lower Jurassic of the High Atlas, Morocco and Tethyan Himalaya, southern Xizang (Tibet), China - Fu-Lin Li; Kai Ye; Xin Rao; Zhong Han; Cheng-Gang Wang; Xiong-Wei Zeng; Long Wang; Hao Liu; Zong-Xin Wang; Fa-Fu Wu; Kun Liang; Wen-Kun Qie (Palaeoworld, 2026)

Neuro-inspired tactile system for robotic embodied perception - Yiyang Li; Ning Li; Herong Wang; Xiaojian Rao; Han Liu; Yue Jiang; Weiguan Zhang; Yue Xiao; Yong Tian; Lin Fan; Jindong Tian (Chemical Engineering Journal, 2026)

Landslide susceptibility assessment based on Bayesian optimization and geographical similarity - Jiayu Yan; Shengwu Qin; Wendi Rao; Chaobiao Zhang; Jiangfeng Lv; Zhijun Lin; Feng Wan; Jiasheng Cao (Natural Hazards, 2026)

Deformation response and damage evolution of subway station under earthquake and post-earthquake fire - Jun-Xing Rao; Zhen-Dong Cui; Zhang-Lin Zhu; Ke-Xuan Li (Tunnelling and Underground Space Technology, 2026)

Rambutan-inspired tri-layer architecture with regulated strain and lithium transport for high-capacity and stable lithium storage - Huan Du; Ganggang Ma; Ziqing Yin; Shaoqing Rao; Sheng Lin; Tianyi Zhang; Jingke Ren; Yucai Wu; Wei Zhang; Ruohan Yu; Dongyuan Zhao; Wei Li; et al. (Science Bulletin, 2026)

Temporal demographic compensation stabilizes pioneer conifer (Pinus massoniana) populations during ecological restoration - Yongwei Luo; Ao Liu; Bingqi Hu; Jinlian Liu; Qifeng Gong; Yan Lin; Jianqiang Rao; Shouzhong Li (Forest Ecology and Management, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Characterization and structural analysis of a novel glucurono-xylanase from Chaetomium fimeti and its potential application in pear juice clarification - Xingyu Liu; Lin Han; Mengqi Liu; Jinglei Wu; Dandan Zhao; Huan Rao; Xia Zhao; Xuechao Zheng; Jianxiong Hao; Xueqiang Liu (Food Research International, 2026)

Enzymatic chain elongation of A-, B-, and C-type grain starches by amylosucrase: Universal structure–function rules for resistant-starch design - Shiyang Li; Yufeng Lin; Zhao Jin; Jiajia Rao; Islam Shahidul; Baochen Fang; Minwei Xu (Food Research International, 2026)

A new fucosylated glucuronoxylomannan from the fruit bodies of Tremella aurantia: structural characterization and immunoenhancing activity on seasonal influenza mRNA vaccine - Jing Chen; Yuan Ma; Zhi-Min Rao; Song-Lin Jiang; Ying-Jun Lou; Karim Malik; Arman Chowdhury; Hua-Zhong Ying; Chen-Huan Yu (Carbohydrate Polymers, 2026)

Cretaceous–Cenozoic tectonic evolution of the central Qiangtang terrane and implications for the initial growth of the Tibetan Plateau - Xiaohui Liu; Yimin Liu; Ying Rao; Yangrui Guo; Xiaoyu Guo; Xingfu Huang; Huilin Li; Lin Ding; Rui Gao (Tectonophysics, 2026)

Sources and distribution of atmospheric microplastics in Northwest China river valleys via land use - Yingquan Li; Wanting Yang; Baowei Zhao; Kaixiang Duan; Lin Rao; Yuda Lin; Guoqiang Liu (Journal of Hazardous Materials, 2026)

Effect of quorum sensing signal molecular analog 4-hydroxy-5-methyl-3(2H)-furanone on the microbial diversity and flavor characteristics of Sichuan Paocai - Chunhui Deng; Qin Peng; Xia Lin; Yue Shu; Shengshuai Li; Yunlong Song; Hong Kong; Lei Liu; Ziwei Liang; Yu Rao (International Journal of Food Microbiology, 2026)

Ecological presence and functional role of bacteriophages in fermented vegetables - Xia Lin; Chunhui Deng; Yue Shu; Shengshuai Li; Yunlong Song; Hong Kong; Ziwei Liang; Lei Liu; Yu Rao (Food Microbiology, 2026)

Correction: Role of tRNA-Derived Fragments and Their Modifications in the Pathogenesis and Treatment of Alzheimer’s Disease - Lin Li; Jianda Kong; Rao Fan; Yang Yuan; Lei Zhu (Molecular Neurobiology, 2026)

Role of tRNA-Derived Fragments and Their Modifications in the Pathogenesis and Treatment of Alzheimer’s Disease - Lin Li; Jianda Kong; Rao Fan; Yang Yuan; Lei Zhu (Molecular Neurobiology, 2026)

Digoxin targets BHLHE40 to inhibit epithelial-mesenchymal transition in cervical cancer cells via downregulation of ANGPTL3 - Canyi Li; Penghua Luo; Lin Tang; Yongqiang Yang; Long Rao; Lijun Zhong (Journal of Natural Medicines, 2026)

Comprehensive risk assessment for five SDHI fungicides with AhR agonistic activity to aquatic ecosystems - Chao Shen; Xiaoyan Ding; Wenhua Rao; Jinfeng Hu; Tao Lin; Xian-zhi Zhou; Yongquan Zheng; Fengshou Dong; Guocheng Fan (Pesticide Biochemistry and Physiology, 2025)

Fluoride removal by MgO-based adsorbents synthesized via distinct routes: Comparative evaluation of adsorption efficiency and column-scale stability - Yee-Rui Chan; Wei-Han Lin; Wei-Zhe Lin; Rao Y. Surampalli; Ying-Liang Yu; Chih-Ming Kao (Journal of Water Process Engineering, 2025)

Strong link in hydrogen isotope ratios between plant α-cellulose and source water for an alpine peatland in the Altai Mountains of northwestern China: Implications for palaeohydrological reconstructions - Fuxi Shi; Zhiguo Rao; Jiantao Cao; Chao Huang; Yunxia Li; Guanghui Lin (Journal of Hydrology, 2025)

Mapping plasma metabolic profiles reflecting air pollution and their association with kidney failure: A prospective cohort study - Peng Hu; Shengtao Wei; Ge Chen; Lan Chen; Fei Tian; Zitong Zhuang; Manting Rao; Zhenhe Huang; Hualiang Lin (Journal of Hazardous Materials, 2025)

Recovery of industrial waste heat for district heating: A complementary heating method and stakeholder coordination - Zichen Rao; Jiayu Li; Pei Liu; Hao Zhou; Yuqing Chen; Hao Fang; Borong Lin (Energy and Buildings, 2025)

Ultrasensitive detection of tsRNA through a transcleavage cross-linking Cas13-Cas14a tool - Gaihua Cao; Qin Wen; Qin Liu; Wei Xu; Jun Rao; Lin Xia; Xi Zhang (Chemical Engineering Journal, 2025)

Distinct cellular localization of α- synuclein and β-synuclein in the chick retina - Fang He; Lin Liu; Shaoxuan Wang; Xin Lin; Guiyu Guan; Xiaoqian Lai; Xi Yu; Xiaotian Wu; Zhihao Shen; Bilin Rao; Mei-Ling Gao; Xuejiao Chen; et al. (Brain Structure and Function, 2025)

Fluoride removal from groundwater via powder-nano MgO adsorption: novel adsorbents development and mechanisms studies novel adsorbents development and mechanisms studies - Jiun-Hau Ou; Ssu-Ching Chen; Wei-Zhe Lin; Francis Verpoort; Rao Y. Surampalli; Chih-Ming Kao (Environmental Science and Pollution Research, 2025)

Late Holocene temperature variability in northern Xinjiang (NW China) and its potential connection to the Atlantic Meridional Overturning Circulation - Ruijin Chen; Aifeng Zhou; Zhiguo Rao; Mingrui Qiang; Panpan Ji; Lin Chen; Haipeng Wang; Jianhui Chen (Quaternary Science Reviews, 2025)

Influence of parameters on dynamic characteristics of friction-induced self-excited vibration in the ship stern shaft seal - Yuze Yang; Xuebing Zhang; Lin Xue; Donglin Zou; Chunxiao Jiao; Jianghai Xu; Na Ta; Zhushi Rao (Ocean Engineering, 2025)

Clay sediment adhesion-dominated clogging and its recovery under infiltration washing in statically compacted pervious concrete - Yu Ding; Yapei Xia; Lin Guo; Qi Wan; Zhenyao Xia; Hai Xiao; Yunkang Rao (Journal of Hydrology, 2025)

Discovery of a novel antibacterial protein from Lactobacillus acidophilus using integrated genomic mining, molecular dynamics, and functional assays - Yubo Zhang; Weiling Lin; Weiying Rao; Binqi He; Tingyi He; Guidong Huang (Food Bioscience, 2025)

First total ozone column observations from the Ozone Monitoring Suite-Nadir (OMS-N) onboard China’s FengYun-3F satellite - Jian Xu; Yapeng Wang; Lin Chen; Dmitry Efremenko; Lanlan Rao; Gegen Tana; Shuanghui Liu; Qian Wang; Jinghua Mao; Yongmei Wang; Ling Sun; Huanhuan Yan; et al. (Science China Earth Sciences, 2025)

Molecular dynamics study on coalescence interface evolution of collided dry ice particles - Lin Teng; Wei Lin; Xin Huang; Zhenchao Li; Hongru Li; Pengbo Yin; Shihang Rao (Process Safety and Environmental Protection, 2025)

From stress to defense: Spatial confinement of nanoplastics in rice root cell walls via pectin matrix remodeling - Chaofa Chen; Jiaji Liu; Chenghua Xing; Xi-Lin Wu; Engao Zhu; Yuchun Rao; Yan Lin; Jianfang Yan; Miaozhen Cai; Hua Zhang; Yongming Luo (Journal of Hazardous Materials, 2025)

Epidemiological characteristics and clinical treatment of melioidosis: a 11-year retrospective cohort study in Hainan - Tianzhou Lan; Guangqiang Zhao; Haichao Liu; Lei Qu; Qingjia Chi; Beibei Meng; Juan Fang; Fang Yang; Zhenhong Hu; Bin Wang; Rong Lin; Chenlong Rao; et al. (Infectious Diseases, 2025)

Effect of substrates on functional microbial communities and functional metabolic pathways of constructed wetlands treating mariculture wastewater - Huidong Zheng; Jinian Rao; Fang Yang; Yongqing Lin; Xueling Wang; Menglu Zhang; Yuchen Zhu (Journal of Environmental Management, 2025)

Complex spatiotemporal heterogeneity in Holocene human activities revealed by pollen and Pb records from major monsoonal China - Xiaoxu Qu; Zhiguo Rao; Zhongwei Shen; Yunxia Li; Lin Zhao; Chao Huang (Anthropocene, 2025)

Greenery strategies for reducing pedestrian particulate exposure along an open-flanked urban arterial road - Zhanyong Wang; Yanying Rao; Xinyuan Lin; Shuting Chen; Xisheng Hu (Urban Climate, 2025)

Adaptive fluoride removal across concentration scales: Potential roles of microbial and acicular gypsum interactions in nitrogen and phosphate cycling - Ying-Liang Yu; Wei-Han Lin; Rao Y. Surampalli; Ssu-Ching Chen; Chih-Ming Kao (Journal of Hazardous Materials, 2025)

Influence of disaccharide and mixed starter cultures on the fermentation process in earthen jar of factory-produced Sichuan paocai - Qiu Zhong; Hua Xiong; Shengshuai Li; Kaiyu Guo; Yue Shu; Xia Lin; Yage Xing; Ziwei Liang; Xingchen Liu; Lei Liu; Yu Rao (Food Research International, 2025)

Can CMIP6 models simulate the ozone valley over the Tibetan plateau in boreal summer? - Lin Shen; Jian Rao; Shuangyan Yang; Dong Guo (Climate Dynamics, 2025)

Developmental expression of α- and β- synuclein in the mouse retina - Wenhui Zhong; Zhongqun Chen; Shaoxuan Wang; Jun Cao; Xin Lin; Xiaoqian Lai; Bilin Rao; Jun Zhang (Brain Structure and Function, 2025)

A decade-long meta-analysis of risks posed by pesticides in Chinese surface waters - Jiuying Li; Lin Hou; Na Liu; Kaifeng Rao; Jing Zheng; Jian Xu; John P. Giesy; Xiaowei Jin (Journal of Environmental Management, 2025)

Rapid evaluation of Curcuma origin and quality based on E-eye, flash GC e-nose, and FT-NIR combined with machine learning technologies - Qiang Guo; Ming-xuan Li; Rao Fu; Xin Wan; Wen-hao Dong; Chun-qin Mao; Zhen-hua Bian; De Ji; Tu-lin Lu; Yu Li (Food Chemistry, 2025)

Green solvent hydrothermal recycling of end-of-life crystalline silicon photovoltaic modules - Kai Zhang; Shihao He; Danyan Qin; Xian Xie; Wei Zhang; Pan Deng; Jintao Li; Hongdan Rao; Heming Deng; Tao Mei; Xianbao Wang; Liangyou Lin (Chemical Engineering Journal, 2025)

Structural analysis and numerical modeling of multi-stage tectonic deformation in the Ziliujing anticline, SW Sichuan Basin, China: Implications for deformation propagation in salt-bearing fold-and-thrust belts - Jiawei Liu; Gang Rao; Sen Bai; Xiaolin Xiong; Jinwu Zhang; Wenxiong Yang; Chao Yin; Yaqi Zhong; Pengcheng Tang; Jianhua Qiu; Lin Gao (Tectonophysics, 2025)

Untargeted metabolomics and network pharmacology reveal the uric acid-lowering effects of alcohol extract of Gnaphalium affine and its extracts in hyperuricemic rats - Chen Wang; Xinchao He; Lijuan Rao; Jiajing Liao; Jin Qian; Xuefeng Yu; Sen Mei; Suqin Lin; Linqian Xu; Guiming Fu; Yin Wan (Food Bioscience, 2025)

Fabrication of sweet potato leaf-derived nanocellulose and its influence on the properties and interactions in peanut protein films - Ming-yang Sun; Yu-qi Yang; Qi Gao; Jia-nan Chen; Chong-ting Guo; Miao Yu; Jia-jia Rao; Xue-jun Gu; You-lin Xue (Food Hydrocolloids, 2025)

An ultrafast dual-channel ratiometric fluorescence probe based on functionalized N-GQDs for dynamic monitoring of salicylic acid in plants - Hou-Yun Huang; A-ling Tang; Feng Gao; Shuai Tan; Zhi-Min Rao; Li-Wei Liu; Shi-Tao Liu; Xiang Zhou; Lin-Lin Yang; Song Yang (Chemical Engineering Journal, 2025)

Scenario forecasting of carbon neutrality by combining the LEAP model and future land-use simulation: An empirical study of Shenzhen, China - Xinyan Zhao; Zhijie Rao; Jinyao Lin; Xinchang Zhang (Sustainable Cities and Society, 2025)

Exposure to toxic metals might accelerate aging - Wenqing Wang; Kaixuan Yang; Jiayi Li; Yaoyao Lin; Man Rao; Yuting Zhang; Hazizi Duoliken; Mingjuan Jin; Jianbing Wang; Kun Chen; Mengling Tang (Environmental Research, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Exploring the relationships among life satisfaction, neighborhood satisfaction and travel satisfaction in Beijing - Jingwen Rao; Haiqing Lin; Jing Ma; Yanwei Chai (Travel Behaviour and Society, 2025)

Zein/EGCG/Ca2+ oleogels for margarine substitution in biscuits: Impact on dough properties and biscuits quality attributes - Qiming Wang; Zhenan Rao; Ling Jiang; Xiaojuan Lei; Jichun Zhao; Lin Lei; Kaihong Zeng; Jian Ming (Food Hydrocolloids, 2025)

Systematical identification of regulatory GPCRs by single-cell trajectory inference reveals the role of ADGRD1 and GPR39 in adipogenesis - Chuan Ye; Xuemei Wang; Jun Lin; Chenyang Wu; Yuhua Gao; Chenghao Guo; Yunxi Liao; Ziyan Rao; Shaodong Huang; Weixuan Chen; Ying Huang; Jinpeng Sun; et al. (Science China Life Sciences, 2025)

Targeting cardiac fibrosis with Chimeric Antigen Receptor-Engineered Cells - Qinghang Zhang; Jinjie Dai; Tianbao Liu; Wutian Rao; Dan Li; Zhengying Gu; Lin Huang; Jiayi Wang; Xumin Hou (Molecular and Cellular Biochemistry, 2025)

Molecular characterization of a novel mycovirus from Curvularia lunata in China - Bin Ke; Xiaohan Mo; Mengting Wu; Lin Wang; Ru Peng; Yuwen Lu; Jiejun Peng; Shaofei Rao; Guanwei Wu; Jianping Chen; Fei Yan; Hongying Zheng (Archives of Virology, 2025)

Bioassay-guided isolation and characterisation of α-glucosidase inhibitors from Sanghuangporus baumii - Xiaoyan Hu; Yanling Wang; Yuhao Lin; Nini Yang; Junyi Yao; Weiguang Shan; Guiwei Rao; Youmin Ying (Natural Product Research, 2025)

Persistence of a shallow-marine environment in the western Kunlun area (northwestern Tibet) until the early Maastrichtian: Evidence from radiolitid rudist bivalves - Bintao Gao; Qinghai Zhang; Xin Rao; Lin Ding (Cretaceous Research, 2025)

Testing and improving brGMGTs-based paleotemperature estimates in peat sediments: Evidence from global surface peat samples and two well-dated Holocene peat cores in far Northwest China - Zhongwei Shen; Minghua Zhao; Tianyan Lin; Xiaoxu Qu; Haichun Guo; Jiantao Cao; Guodong Jia; Zhiguo Rao (Global and Planetary Change, 2025)

Contribution of phosphorylation modification by sodium tripolyphosphate to the functional properties of hollow zein nanoparticles - Sheng-qi Rao; Cao-chen Jia; Lin Du; Wei-biao Zhou; Wen-xuan Hu; Yi Jiang; Zhi-rong Wang; Zhen-quan Yang (Food Research International, 2025)

Exploration of the impact of different drying methods on the quality of Gastrodia elata: A study based on drying kinetics and multidimensional quality evaluation - Ming-xuan Li; Bin Wang; Yu Li; Xin-ru Nie; Jing Mao; Qiang Guo; Nuo Xu; Rao Fu; Zhi-jun Guo; Xiao-li Zhao; Zhen-hua Bian; Tu-lin Lu; et al. (Food Chemistry, 2025)

The characterization of zein/xanthan gum composite oleogel: A comparative study of bioactive substances in interface and oil phases - Hong Chen; Qiming Wang; Sili Liu; Zhenan Rao; Xiaojuan Lei; Jichun Zhao; Lin Lei; Kaihong Zeng; Jian Ming (Food Hydrocolloids, 2025)

Soil microbial diversity in boreal forests of China: A case study of the Altai Mountains with an emphasis on core microbiomes - Gu Rao; Wen-Long Song; Di Lin; Ya-Jing Chen; Shu-Zhen Yan; Shuang-Lin Chen (Applied Soil Ecology, 2025)

Rapid screening of pottery lipid residue profile via comprehensive two-dimensional gas chromatography - Bin Han; Nanning Lyu; Long Yan; Tao Wang; Jie Gao; Liugen Lin; Huiyun Rao; Yimin Yang (Analytica Chimica Acta, 2025)

Oleogels loaded with lycopene structured using Zein/EGCG/Ca2+ complexes: Preparation, characterization and potential application - Qiming Wang; Zhenan Rao; Ling Jiang; Xiaojuan Lei; Jichun Zhao; Lin Lei; Kaihong Zeng; Jian Ming (Food Chemistry, 2025)

Investigating the interaction mechanisms between arachin and resveratrol: Utilizing multi-spectroscopy and computational chemistry - Yu-qi Yang; Qi Gao; Shi-qi Yue; Xue Peng; Ning Wang; Jing-li Xin; Miao Yu; Jia-jia Rao; You-lin Xue (Food Chemistry, 2025)

The assembly mechanism of Zein/EGCG/PEG nanoparticles in a water system and their adsorption behavior at the oil-water interface - Qiming Wang; Zhenan Rao; Ling Jiang; Xiaojuan Lei; Jichun Zhao; Lin Lei; Kaihong Zeng; Jian Ming (Food Chemistry, 2025)

3,5-Dicaffeoylquinic acid promotes intestinal urate excretion via the MAPK signaling pathway based on Caco-2 Cell model - Jiajing Liao; Jin Qian; Lijuan Rao; Suqin Lin; Chen Wang; Linqian Xu; Bing Yuan; Jiayi Yuan; Yin Wan; Guiming Fu (Food Bioscience, 2025)

Strong and tough anisotropic short-chain chitosan-based hydrogels with optimized sensing properties for flexible strain sensors - Huijuan Lin; Wenlong Yuan; Wencan Zhang; Rao Dai; Tian Zhang; Yueyun Li; Shuanhong Ma; Shasha Song (Carbohydrate Polymers, 2025)

Microglia heterogeneity during neuroinflammation and neurodegeneration in the mouse retina - Bilin Rao; Xiaoqing Liu; Jiayi Xiao; Xiaotian Wu; Fang He; Qingwen Yang; Wenna Zhao; Xin Lin; Jun Zhang (Brain Structure and Function, 2024)

DNA Barcodes for Identifying Fish Egg Species Diversity in Summer and Autumn in the Southwest Daya Bay, China - Shile Zheng; Jianbin Lin; Fengxia Wu; Yiyong Rao; Jinrun Wang; Siyuan He; Honghui Huang; Gang Hou (Fishes, 2024)
Identifying fish eggs and understanding fish reproductive periods are necessary for informed fishery management. However, accurate the identification of fish eggs is difficult because eggs have few distinct characters, and their morphology varies ontogenetically. Using cytochrome c oxidase subunit I, we identified fish eggs from ichthyoplankton samples collected in the summer and autumn of 2021 from southwestern Daya Bay, China. Of 567 fish eggs, 498 high-quality cytochrome c oxidase subunit I sequences were obtained, of which 116 eggs (23.3%) could be identified to species; 364 (73.1%) to genus, family and/or order; and 18 (3.6%) could not be assigned. Of 51 apparent taxa, 46 were identified to 6 orders, 19 families, and 30 genera; 20 to the species and 25 to the genus and/or family, and 1 to the order. Among these 51 taxa, 35 occurred in summer, 29 occurred in autumn, and 13 occurred in both seasons; 22 occurred only in summer and 16 only in autumn, indicating species-specific spawning periods. High-resolution photographs of eggs are provided to facilitate subsequent identification based on morphology. These results will facilitate the identification of spawning grounds and their protection, to more holistically manage fishery resources in Daya Bay, China.

ROS responsive nanozyme loaded with STING silencing for the treatment of sepsis-induced acute lung injury - Yin-jin Zhang; Ling-yang Chen; Feng Lin; Xia Zhang; Hai-fei Xiang; Qing Rao (Toxicology and Applied Pharmacology, 2024)

Polygonati Rhizoma varieties and origins traceability based on multivariate data fusion combined with an artificial intelligence classification algorithm - Peng Chen; Chenghao Fei; Rao Fu; Xiaoyan Xiao; Yuwen Qin; Xiaoman Li; Zhijun Guo; Jianmin Huang; De Ji; Lin Li; Tulin Lu; Qiaosheng Guo; et al. (Food Chemistry, 2024)

Control of stepwise subduction and slab breakoff on volcanism and uplift in the Tibetan Plateau - Jian Wang; Zhi Wang; Xiugen Fu; Xuan-Ce Wang; Simon A. Wilde; Yi Fu; Jian Lin; Hengye Wei; Lijun Shen; Gang Rao; Ahmed Mansour (Earth and Planetary Science Letters, 2024)

Phytotoxicity of Prussian blue nanoparticles to rice and the related defence mechanisms: In vivo observations and physiological and biochemical analysis - Kai Xu; Yilun Lan; Chenghua Xing; Yuchun Rao; Engao Zhu; Jianfang Yan; Shaobin Wang; Xi-Lin Wu; Miaozhen Cai; Xiaoguang Duan (Chemosphere, 2024)

Response of N, P, and metal ions in deep soil layers to long-term cultivation of rubber and rubber-based agroforestry systems - Chang-An Liu; Yu Nie; Jia-Lin Zhang; Jian-Wei Tang; Xin Rao; Kadambot H.M. Siddique (Science of The Total Environment, 2024)

Influence of vegetation type on brGDGTs: Results from surface soils beneath sub-alpine forest and grassland under the same climatic conditions - Shikai Wei; Tianyan Lin; Yunxia Li; Jiantao Cao; Guodong Jia; Mingzhi Chen; Zhiguo Rao (Organic Geochemistry, 2024)

Understanding Consumer Preferences for Attributes of Yak Meat: Implications for Economic Growth and Resource Efficiency in Pastoral Areas - Yongshun Ai; Rao Yuan; Shaosheng Jin; Wen Lin; Yan Zhang (Meat Science, 2024)

Climate synergistic benefits: A path to the Beautiful China through total control of major air pollutants - Xi Cheng; Zhong-Xing Zhang; Ting Shi; Nian Yang; Shu-Hao Yang; Jian-Lin Chen; Guo-Zhu Mao; Ze-Feng Qi; Sheng Rao; Chun-Lai Jiang (Journal of Cleaner Production, 2024)

Investigating the impact of ultrasound on the structural, physicochemical, and emulsifying characteristics of Dioscorin: Insights from experimental data and molecular dynamics simulation - Qi Gao; Yu-qi Yang; Hao-nan Nie; Bing-qing Wang; Xue Peng; Ning Wang; Jiang-kuo Li; Jia-jia Rao; You-lin Xue (Food Chemistry, 2024)

High internal phase pickering emulsions stabilized by zein/whey protein nanofibril complexes: Preparation and lycopene loading - Shasha Xia; Qiming Wang; Zhenan Rao; Xiaojuan Lei; Jichun Zhao; Lin Lei; Jian Ming (Food Chemistry, 2024)

Epigenetic modifications of gonadotropin receptors can regulate follicular development - Yanyan Yang; Wanyou Feng; Jinhua Zhou; Ruimen Zhang; Xinyue Lin; Suren Rao Sooranna; Yanfei Deng; Deshun Shi (Animal Reproduction Science, 2024)

Increasing tree diversity reduces spatial heterogeneity of soil organic carbon and promotes carbon storage in subtropical forests - Muhammed Mustapha Ibrahim; Yongbiao Lin; Zhifeng Guo; Conghui Guo; Xingquan Rao; Suping Liu; Shenglei Fu; Qing Ye; Enqing Hou (Agriculture, Ecosystems & Environment, 2024)

Formulation and characterization of bigels utilizing whey protein and polysaccharides: Potential applications as cream analogues - Ling Jiang; Qiming Wang; Zhenan Rao; Xiaojuan Lei; Jichun Zhao; Lin Lei; Jian Ming (Food Hydrocolloids, 2024)

Cell-specific localization of β-synuclein in the mouse retina - Wenhui Zhong; Qingwen Yang; Fenglan Wang; Xin Lin; Zhongqun Chen; Jing Xue; Wenna Zhao; Xiaoqing Liu; Bilin Rao; Jun Zhang (Brain Structure and Function, 2024)

Transmission characteristics and the factors influencing stable oxygen isotopes in precipitation, soil water, and drip water in Remi Cave, Western Hunan, China - Yiping Tian; Yunxia Li; Jiayan Li; Chenxi Yang; Angli Du; Miaofa Li; Xinping Zhang; Lin Zhao; Lidan Liu; Zhiguo Rao (Journal of Hydrology, 2024)

Investigation into the potential mechanism of Bacillus amyloliquefaciens in the fermentation of broad bean paste by metabolomics and transcriptomics - Hongbin Lin; Shiqi Liao; Zesu Zhou; Ziting Yan; Jianhua Zhao; Yue Xiang; Min Xu; Jie Zhao; Ping Liu; Wengwu Ding; Yu Rao; Jie Tang (Food Research International, 2024)

Straw management adopted by large farms sustains grain yield but mitigates greenhouse gas emissions - Zhenzhen Li; Yong Lin; Zheng-Rong Kan; Sana ur Rehman; Atta Mohi Ud Din; Feng-Min Li; Shixiang Zhang; Ping Wu; Yingfu Ding; Chensheng Xu; Congying Rao; Huaxin Dai; et al. (Field Crops Research, 2024)

A modified drag coefficient model for calculating the terminal settling velocity and horizontal diffusion distance of irregular plume particles in deep-sea mining - Ze-lin Liu; Qiu-hua Rao; Wei Yi; Wei Huang (Environmental Science and Pollution Research, 2024)

PM2.5-induced premature senescence in HUVECs through the SIRT1/PGC-1α/SIRT3 pathway - Qing Yan; Rao Zheng; Yi Li; Juan Hu; Meidi Gong; Manman Lin; Xuecong Xu; Jing Wu; Shikun Sun (Science of The Total Environment, 2024)

Probiotic fermentation affects the chemical characteristics of coix seed-chrysanthemum beverage: Regulatory role in sensory and nutritional qualities - Huishan Rao; Lianzhu Lin; Mouming Zhao (Food Bioscience, 2024)

Chemical composition, sources, and processes of winter haze in Chengdu, China: Insights from integrating the bulk chemical and single particle approaches - Junke Zhang; Wei Sun; Yunfei Su; Xiaoxue Peng; Chunying Chen; Xinyi Fu; Yuhan Long; Gehui Wang; Zhihan Rao; Lin Han; Xiaojuan Huang (Atmospheric Environment, 2024)

Jurassic integrative stratigraphy, biotas, and paleogeographical evolution of the Qinghai-Tibetan Plateau and its surrounding areas - Jianguo Li; Xin Rao; Lin Mu; Xiaohui Cui; Xin Li; Hui Luo; Peixue Liu (Science China Earth Sciences, 2024)

Ecological and human health hazards of soil heavy metals after wildfire: A case study of Liangshan Yi autonomous prefecture, China - Lin Rao; Chao Zheng; Jian-Bin Chen; Jun-Zhuo Cai; Zhan-Biao Yang; Xiao-Xun Xu; Guo-Chun Lv; Chang-Lian Xu; Gui-Yin Wang; Yu-Bon Man; Ming-Hung Wong; Zhang Cheng (Chemosphere, 2024)

Influence of propulsion shafting longitudinal vibration on the excitation force and vortex dynamics characteristics of pump-jet propulsor - Donglin Zou; Lin Xue; Qiang Lin; Jianghai Xu; Xinguo Dong; Na Ta; Zhushi Rao (Ocean Engineering, 2024)

Quantitative Holocene climate reconstruction and anthropogenic impact analysis based on the pollen records in peat sediment in Southern China - Lin Zhao; Yaoyao Zeng; Zhiguo Rao; Chao Huang; Yunxia Li; Lidan Liu; Chunmei Ma (Global and Planetary Change, 2024)

Elucidating the links between N2O dynamics and changes in microbial communities following saltwater intrusions - Rongrong Xie; Laichang Lin; Chengchun Shi; Peng Zhang; Peiyuan Rao; Jiabing Li; Dandan Izabel-Shen (Environmental Research, 2024)

Sedimentary brGDGTs in China: An overview of modern observations and proposed land Holocene paleotemperature records - Tianyan Lin; Zhiguo Rao; Yaoyao Zeng; Yunxia Li; Lin Zhao; Lidan Liu; Xiong Xiao; Cicheng Zhang; Zhongwei Shen; Jiantao Cao; Guodong Jia (Earth-Science Reviews, 2024)

Deciphering the effects of crop rotation on tobacco bacterial wilt through general and specific disease suppression - Hai-kun Ma; Zhi-jiang Wang; Meng-jiao Li; Qing-lin Rao; Jun Cai; Xiao-fei Gu (European Journal of Plant Pathology, 2024)

Natural and anthropogenic controls on environmental change during the Holocene based on a multi-proxy record obtained from subalpine peatland in southern China - Xiaoxu Qu; Chao Huang; Zhiguo Rao; Liyuan Wu; Yongyi Luo; Fajin Chen; YunXia Li; Lin Zhao; Lidan Liu; Zhiguang Song; Wenfeng Deng (Science of The Total Environment, 2024)

Holocene provenance variations and palaeofloods response to ENSO-driven monsoon precipitation in the subalpine peatland in southern China - Xiaoxu Qu; Chao Huang; Zhiguo Rao; Gangjian Wei; Liyuan Wu; Yongyi Luo; Yunxia Li; Lin Zhao; Lidan Liu; Wenfeng Deng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Degradation of indoor formaldehyde by the flexible porous material loaded photocatalyst - Gao Yi; Lin zhe; Zhou huipeng; Zhang Yuxin; Zhang Tianhu; Rao Yandi (Journal of Environmental Chemical Engineering, 2024)

Biological upgrading of biogas assisted with membrane supplied hydrogen gas in a three-phase upflow reactor - Yue Rao; Tzu-Yu Lin; Fangqiong Ling; Zhen He (Bioresource Technology, 2024)

Novel cytochrome P450s for various hydroxylation of steroids from filamentous fungi - Guojuan Yi; Hanlu Zou; Tao Long; Tolbert Osire; Lin Wang; Xiaoyun Wei; Mengfei Long; Zhiming Rao; Guojian Liao (Bioresource Technology, 2024)

Fabrication and characterization of oleogels stabilized by metal-phenolic network coatings-decorated zein nanoparticles - Qiming Wang; Zhenan Rao; Yuanyuan Chen; Ling Jiang; Xiaojuan Lei; Jichun Zhao; Fuhua Li; Lin Lei; Jian Ming (Food Chemistry, 2024)

Cheap organocatalyst diphenyl phosphate for efficient chemical recycling of poly(lactic acid), other polyesters and polycarbonates - Wanhua Wu; Huajuan Zhai; Kaiting Wu; Xin Wang; Weihan Rao; Jiandong Ding; Lin Yu (Chemical Engineering Journal, 2024)

Prediction of urban residential energy consumption intensity in China toward 2060 under regional development scenarios - Shuqin Chen; Yurui Huang; Jiamin Hu; Shichao Yang; Changqing Lin; Kai Mao; Zhiqin Rao; Yue Chen (Sustainable Cities and Society, 2023)

Study of the impact of digitization on the carbon emission intensity of agricultural production in China - Liping Zhao; Xi Rao; Qiaowen Lin (Science of The Total Environment, 2023)

Preclinical evaluation of RQ3013, a broad-spectrum mRNA vaccine against SARS-CoV-2 variants - Shudan Tan; Jinghua Zhao; Xue Hu; Yufeng Li; Zihan Wu; Guoliang Lu; Zhaoli Yu; Binhe Du; Yan Liu; Li Li; Yuchen Chen; Ye Li; et al. (Science Bulletin, 2023)

Phytolith-reconstructed Holocene vegetation dynamics from a subalpine peat deposit in the mid-subtropical zone of China - Lidan Liu; Hengyu Liu; Zhiguo Rao; Chao Huang; Lin Zhao; Yunxia Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Remediation of diesel-oil contaminated soils using an innovative nanobubble and electrolyzed catalytic system - Wei-Ting Chen; Justin Chun-Te Lin; Shih-Hsiung Chen; Francis Verpoort; Kun-Liang Hong; Rao Y. Surampalli; Chih-Ming Kao (Journal of Cleaner Production, 2023)

Dual-channel MIRECL portable devices with impedance effect coupled smartphone and machine learning system for tyramine identification and quantification - Zhiwei Lu; Jun Qin; Chun Wu; Jiajian Yin; Mengmeng Sun; Gehong Su; Xianxing Wang; Yanying Wang; Jianshan Ye; Tao Liu; Hanbing Rao; Lin Feng (Food Chemistry, 2023)

Construction of galangin-loaded soy extract nanoparticles using pH-driven method: Process optimization, stability evaluation, and structure characterization - Huishan Rao; Fei Chen; Lianzhu Lin; Mouming Zhao (Food Hydrocolloids, 2023)

The linear/nonlinear rheological behaviors of Pickering emulsion stabilized by Zein and Xanthan gum: Effect of interfacial assembly strategies - Hong Chen; Qiming Wang; Zhenan Rao; Xiaojuan Lei; Jichun Zhao; Lin Lei; Jian Ming (Food Hydrocolloids, 2023)

STAT6 promoting oxalate crystal deposition-induced renal fibrosis by mediating macrophage-to-myofibroblast transition via inhibiting fatty acid oxidation - Tianhui Yuan; Yuqi Xia; Shengyu Pan; Bojun Li; Zehua Ye; Xinzhou Yan; Weimin Hu; Lei Li; Baofeng Song; Weimin Yu; Haoyong Li; Ting Rao; et al. (Inflammation Research, 2023)

Distribution, assembly, and interactions of soil microorganisms in the bright coniferous forest area of China's cold temperate zone - Gu Rao; Shu-Zhen Yan; Wen-Long Song; Di Lin; Ya-Jing Chen; Shuang-Lin Chen (Science of The Total Environment, 2023)

Single-cell dynamics of liver development in postnatal pigs - Lin Rao; Liping Cai; Lusheng Huang (Science Bulletin, 2023)

Developmental dynamics of the single nucleus regulatory landscape of pig hippocampus - Siyu Yang; Dong Chen; Lei Xie; Xiaoxiao Zou; Yanyuan Xiao; Lin Rao; Tianxiong Yao; Qing Zhang; Liping Cai; Fei Huang; Bin Yang; Lusheng Huang (Science China Life Sciences, 2023)

Complete genome sequence of a novel mitovirus detected in Colocasia esculenta - Mengting Wu; Chanchan Huang; Lin Wang; Bin Ke; Yuwen Lu; Jiejun Peng; Shaofei Rao; Guanwei Wu; Jianping Chen; Hongying Zheng; Fei Yan (Archives of Virology, 2023)

Regulation on copper-tolerance in Citrus sinensis seedlings by boron addition: Insights from root exudates, related metabolism, and gene expression - Huan-Huan Chen; Zhi-Chao Zheng; Wen-Shu Chen; Rong-Yu Rao; Xu-Feng Chen; Xin Ye; Jiuxin Guo; Lin-Tong Yang; Li-Song Chen (Journal of Hazardous Materials, 2023)

Synergistic enhanced activation of peroxymonosulfate by heterojunction Co3O4–CuO@CN for removal of oxytetracycline: Performance, mechanism, and stability - Ning Li; Huanxuan Li; Chen Xu; Zhong Zhou; Tao Rao; Ran Ji; Sihang Lin; Jia Du; Shaodan Xu; Shuguang Lyu; Feng Li; Junhong Tang (Environmental Research, 2023)

Impact of lignin constituents on the bacterial community and polycyclic aromatic hydrocarbon co-metabolism in an agricultural soil - Leizhen Rao; Decheng Gu; Xingjia Xiang; Jun Zeng; Yucheng Wu; Xiangui Lin; Peter Christie (Environmental Pollution, 2023)

Distribution and synaptic organization of substance P-like immunoreactive neurons in the mouse retina - Fenglan Wang; Wenhui Zhong; Qingwen Yang; Wenna Zhao; Xiaoqing Liu; Bilin Rao; Xin Lin; Jun Zhang (Brain Structure and Function, 2023)

Numerical examination of the geomorphic indicators for lateral fold growth - Lin Gao; Chuanqi He; Gang Rao; Ci-Jian Yang; Xiaoping Yuan; Jingtao Lai; Pengcheng Tang; Lei Wu (Geomorphology, 2023)

Corrigendum to “Insights into a novel chrysanthemum-coix seed beverage prepared by enzymatic hydrolysis: Chemical profile, sensory quality, and functional property” [Food Bioscience 52 (2023) 102490] - Huishan Rao; Lianzhu Lin; Mouming Zhao (Food Bioscience, 2023)

5-epi-ent-Kaurane diterpenoids from the aerial parts of Isodon eriocalyx and their anti-atherosclerotic potential - Long Mu; Tian Li; Peng-Lin Wu; Ling-Qiao Cai; Shu-Ying Li; Zi-Yuan Wang; Yuan-Yuan Liu; Jie Wang; Dong Yan; Zheng-Yun Rao; Chao-Jun Wang; Jian Zhang; et al. (Phytochemistry, 2023)

Complete nucleotide sequence of hackberry virus A, a tentative member of the genus Waikavirus - Jiajia Weng; Mengting Wu; Zhuangxin Ye; Lin Wang; Bin Ke; Chanchan Huang; Yuwen Lu; Jiejun Peng; Lin Lin; Shaofei Rao; Guanwei Wu; Jianping Chen; et al. (Archives of Virology, 2023)

Contrasting responses of bacterial community to 4,4′-dibromodiphenyl ether (BDE-15) contamination in soil microcosms at different temperatures - Pengfei Shao; Shasha Fang; Leizhen Rao; Xi Wang; Jun Zeng; Shimin Zhang; Yucheng Wu; Jun Yao; Xiangui Lin (Chemosphere, 2023)

Insights into a novel chrysanthemum-coix seed beverage prepared by enzymatic hydrolysis: Chemical profile, sensory quality, and functional property - Huishan Rao; Lianzhu Lin; Mouming Zhao (Food Bioscience, 2023)

Forecasting the carbon emissions in Hubei Province under the background of carbon neutrality: a novel STIRPAT extended model with ridge regression and scenario analysis - Congjun Rao; Qifan Huang; Lin Chen; Mark Goh; Zhuo Hu (Environmental Science and Pollution Research, 2023)

Quantification and visualization of meat quality traits in pork using hyperspectral imaging - Xi Tang; Lin Rao; Lei Xie; Min Yan; Zuoquan Chen; Siyi Liu; Liqing Chen; Shijun Xiao; Nengshui Ding; Zhiyan Zhang; Lusheng Huang (Meat Science, 2023)

Identification and validation of reference genes for qRT-PCR analyses under different experimental conditions in Allium wallichii - Ying Lin; Guofeng Liu; Ying Rao; Bo Wang; Ruifeng Tian; Yuanyuan Tan; Ting Peng (Journal of Plant Physiology, 2023)

RBM3 interacts with Raptor to regulate autophagy and protect cardiomyocytes from ischemia–reperfusion-induced injury - Nan Wang; Limeiting Wang; Changyan Li; Peng Rao; Xun Wang; Yazhou Xu; Lin Yang; Lin Sun; Di Lu (Journal of Physiology and Biochemistry, 2023)

Novel fast pesticides extraction (FaPEx) strategy coupled with UHPLC-MS/MS for rapid monitoring of emerging pollutant fipronil and its metabolite in food and environmental samples - Raghavendra Rao Pasupuleti; Yi-Jia Ku; Tseng-Yu Tsai; Hung-Ta Hua; Yu-Chia Lin; Jentaie Shiea; Po-Chin Huang; Gangadhar Andaluri; Vinoth Kumar Ponnusamy (Environmental Research, 2023)

The resting-state topological organization damage of language-related brain regions in post-stroke cognitive impairment - Sirui Wang; Bo Rao; Guofu Miao; Xin Zhang; Jun Zheng; Junbin Lin; Minhua Yu; Xiaoli Zhou; Haibo Xu; Weijing Liao (Brain Imaging and Behavior, 2022)

Synergistic gel formation in geopolymers of superior mechanical strength synthesized with volcanic ash and slag - Yanjin Zheng; Feng Rao; Xiang Tian; Shengjian Lin (Environmental Science and Pollution Research, 2022)

Do pilot free trade zones improve the green total factor productivity? Evidence from a quasi-natural experiment in China - Aiping Wang; Yao Hu; Yueyue Li; Siqi Rao; Weifen Lin (Environmental Science and Pollution Research, 2022)

Analytical modelling of the mechanical damage of soil induced by lightning strikes capturing electro-thermal, thermo-osmotic, and electro-osmotic effects - Ping-ping Rao; Pei-hao Ouyang; Sanjay Nimbalkar; Qing-sheng Chen; Zhi-lin Wu; Ji-fei Cui (Journal of Mountain Science, 2022)

Comparison of the Macrozoobenthic Community and Sedimentary Environment with and Without Horseshoe Crab Presence in the Crocodile Island Intertidal Zone, Xiamen, China - Lizhe Cai; Xiaoyu Zhao; Wenqing Peng; Jingxiang Lin; Deyuan Yang; Yiyong Rao; Sujing Fu; Xinwei Chen; Wenzhi Cao (Journal of Ocean University of China, 2022)

Genotyping and phenotyping of Lactococcus garvieae isolates from fish by pulse‐field gel electrophoresis (PFGE) and electron microscopy indicate geographical and capsular variations - Shreesha Rao; Mei‐Yun Chen; Chiranan Sudpraseart; Peiry Lin; Terutoyo Yoshida; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2022)
Lactococcus garvieae is the etiological agent of Lactococcosis, an evolving disease affecting many fish species and causing significant economic losses worldwide. Assessing pathogen relatedness and bacterial population structure is critical for determining the epidemiology of L. garvieae infections and in establishing effective pathogen management methods. The previously published morphological and genetic studies point to a clonal population structure, as seen in other fish bacteria. In the present study, the pulsed‐field gel electrophoresis (PFGE) method was utilized to define a population of 41 Taiwanese isolates from outbreaks with comparisons to four well‐characterized non‐Taiwanese isolates previously published. Two restriction enzymes ( Apa I and Sma I) were utilized individually for PFGE analysis (cut‐off value = 90.0%), revealing genetic heterogeneity across L. garvieae isolates, with Apa I and Sma I yielding 12 and seven distinct PFGE band patterns, respectively. The phylogenic analysis using internal transcribed spacer region clustered all L. garvieae isolates in the same clad. Furthermore, the electron microscopic results confirmed the absence of capsular gene cluster (CGC) in previously characterized Taiwanese vaccine strain (S3) from grey mullet. Overall, our findings emphasize the importance of analysing the morphological and genetic diversity in L. garvieae being correlated for proper taxonomic classification in vaccine strain selection and epidemiological studies.

Excavation at Hanjing site yields evidence of early rice cultivation in the Huai River more than 8000 years ago - Zhenwei Qiu; Lina Zhuang; Huiyun Rao; Liugen Lin; Yijie Zhuang (Science China Earth Sciences, 2022)

Cytotoxic α-pyrone derivatives from Cryptocarya yunnanensis - Qian He; Yue Fan; Yu Liu; Yun-Xia You; Li Rao; Yu Su; You-Kai Xu; Bin Lin; Chuan-Rui Zhang (Natural Product Research, 2022)

Complete genome sequence of a putative novel ilarvirus isolated from Eleocharis dulcis - Lanqing Lv; Xinyang Wu; Jiajia Weng; Yuchao Lai; Kelei Han; Yuwen Lu; Jiejun Peng; Lin Lin; Shaofei Rao; Guanwei Wu; Jianping Chen; Hongying Zheng; et al. (Archives of Virology, 2021)

Role of the microRNA-29 family in myocardial fibrosis - Changyan Li; Nan Wang; Peng Rao; Limeiting Wang; Di Lu; Lin Sun (Journal of Physiology and Biochemistry, 2021)

Air-pollutant mass concentration changes during COVID-19 pandemic in Shanghai, China - Zhi Niu; Tingting Hu; Lin Kong; Wenqi Zhang; Pinhua Rao; Dafeng Ge; Mengge Zhou; Yuseng Duan (Air Quality, Atmosphere & Health, 2021)

Complete genome sequence of a novel foveavirus isolated from Allium sativum L. in China - Qi Luo; Shuzhen Hu; Qi Lin; Fei Xu; Jiejun Peng; Hongying Zheng; Guanwei Wu; Shaofei Rao; Jianping Chen; Yuwen Lu; Fengling Guo; Fei Yan (Archives of Virology, 2021)

Mechanism of contractile dysfunction induced by serotonin in coronary artery in spontaneously hypertensive rats - Hao Wang; Xiao-Yan Gao; Fang Rao; Hui Yang; Zhao-Yu Wang; Lin Liu; Su-Juan Kuang; Qi Wu; Chun-Yu Deng; Jing-Song Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Genetic diversity analysis reveals new badnaviruses infecting banana in South China - Xue-Qin Rao; Zi-Lin Wu; Wan Wang; Lin Zhou; Jie Sun; Hua-Ping Li (Journal of Plant Pathology, 2020)

Triptolide suppresses pancreatic cancer cell proliferation by inhibiting hedgehog signaling pathway activity - Juanjuan Feng; Mingjin Rao; Man Wang; Lin Liang; Zhi Chen; Xiufeng Pang; Weiqiang Lu; Zhenliang Sun (Science China Life Sciences, 2019)

Pseudomonas ovata sp. nov., Isolated from the Skin of the Tail of Farmed Murray cod (Maccullochella peelii peelii) with a Profound Ulceration - Qiuhua Rao; Yang Liu; Can Chen; Qiu Lin; Lihua Ren; Minmin Huang; Jiefeng Tu; Tuyan Luo (Current Microbiology, 2019)

The Eurasian Jet Streams as Conduits for East Asian Monsoon Variability - Jasti S. Chowdary; Kaiming Hu; G. Srinivas; Yu Kosaka; Lin Wang; K. Koteswara Rao (Current Climate Change Reports, 2019)

Population pharmacokinetics of oxcarbazepine active metabolite in Chinese paediatric epilepsy patients and its application in individualised dosage regimens - Wei-wei Lin; Xi-wen Li; Zheng Jiao; Jin Zhang; Xin Rao; Da-yong Zeng; Xin-hua Lin; Chang-lian Wang (European Journal of Clinical Pharmacology, 2019)

Chemical composition, antioxidant, antibacterial and cytotoxic activities of essential oil of Leontopodium leontopodioides (Willd.) Beauverd - Yang Gao; Huijuanzi Rao; Ling-Jing Mao; Qing-Lin Ma (Natural Product Research, 2019)

Atorvastatin ameliorates the contractile dysfunction of the aorta induced by organ culture - Feng Zhou; Fang Rao; You-Qing Deng; Hui Yang; Su-Juan Kuang; Fei-Long Wu; Shu-Lin Wu; Yu-Mei Xue; Xiao-Mu Wu; Chun-Yu Deng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

DNA barcoding of traded shark fins, meat and mobulid gill plates in Singapore uncovers numerous threatened species - Benjamin J. Wainwright; Yin Cheong Aden Ip; Mei Lin Neo; Jia Jin Marc Chang; Chester Zhikai Gan; Naomi Clark-Shen; Danwei Huang; Madhu Rao (Conservation Genetics, 2018)

Transferrin receptors-targeting nanocarriers for efficient targeted delivery and transcytosis of drugs into the brain tumors: a review of recent advancements and emerging trends - Hira Choudhury; Manisha Pandey; Pei Xin Chin; Yee Lin Phang; Jeng Yuen Cheah; Shu Chien Ooi; Kit-Kay Mak; Mallikarjuna Rao Pichika; Prashant Kesharwani; Zahid Hussain; Bapi Gorain (Drug Delivery and Translational Research, 2018)

Microalga Isochrysis galbana in feed for Trachinotus ovatus: effect on growth performance and fatty acid composition of fish fillet and liver - Yongjin He; Gang Lin; Xiaozhen Rao; Langjun Chen; Huang Jian; Mingzi Wang; Zheng Guo; Bilian Chen (Aquaculture International, 2018)

Responses of Tree Transpiration and Growth to Seasonal Rainfall Redistribution in a Subtropical Evergreen Broad-Leaved Forest - Yanting Hu; Ping Zhao; Weijun Shen; Liwei Zhu; Guangyan Ni; Xiuhua Zhao; Zhenzhen Zhang; Xingquan Rao; Lei Ouyang; Xiaomin Zeng; Dan Sun; Yongbiao Lin (Ecosystems, 2018)

Limit analysis approach for accessing stability of three-dimensional (3-D) slopes reinforced with piles - Pingping Rao; Linxue Zhao; Qingsheng Chen; Lin Li (Marine Georesources & Geotechnology, 2017)

regSNPs-splicing: a tool for prioritizing synonymous single-nucleotide substitution - Xinjun Zhang; Meng Li; Hai Lin; Xi Rao; Weixing Feng; Yuedong Yang; Matthew Mort; David N. Cooper; Yue Wang; Yadong Wang; Clark Wells; Yaoqi Zhou; et al. (Human Genetics, 2017)

Relationship between landslides and active normal faulting in the epicentral area of the AD 1556 M~8.5 Huaxian Earthquake, SE Weihe Graben (Central China) - Gang Rao; Yali Cheng; Aiming Lin; Bing Yan (Journal of Earth Science, 2017)

Urban high-resolution fossil fuel CO2 emissions quantification and exploration of emission drivers for potential policy applications - Risa Patarasuk; Kevin Robert Gurney; Darragh O’Keeffe; Yang Song; Jianhua Huang; Preeti Rao; Martin Buchert; John C. Lin; Daniel Mendoza; James R. Ehleringer (Urban Ecosystems, 2016)

Millennium recurrence interval of morphogenic earthquakes on the Qingchuan fault, northeastern segment of the Longmen Shan Thrust Belt, China - Aiming Lin; Bing Yan; Gang Rao (Journal of Seismology, 2016)

Species-specific differences in the role of L-type Ca2+ channels in the regulation of coronary arterial smooth muscle contraction - Hui Yang; Su-Juan Kuang; Fang Rao; Yu-Mei Xue; Xiao-Ying Liu; Zhi-Xin Shan; Xiao-Hong Li; Jie-Ning Zhu; Zhi-Ling Zhou; Xiao-juan Zhang; Qiu-Xiong Lin; Xi-Yong Yu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Probing the Neural Basis of Superstition - Li-Lin Rao; Yu Zheng; Yuan Zhou; Shu Li (Brain Topography, 2014)

Prediction of protein structural classes based on feature selection technique - Hui Ding; Hao Lin; Wei Chen; Zi-Qiang Li; Feng-Biao Guo; Jian Huang; Nini Rao (Interdisciplinary Sciences: Computational Life Sciences, 2014)

Seasonal dynamics of physical and biological processes in the central California Current System: A modeling study - Lin Guo; Fei Chai; Peng Xiu; Huijie Xue; Shivanesh Rao; Yuguang Liu; Francisco P. Chavez (Ocean Dynamics, 2014)

Genetic variation at 8q24, family history of cancer, and upper gastrointestinal cancers in a Chinese population - Heather P. Tarleton; Shen-Chih Chang; Sungshim Lani Park; Lin Cai; Baoguo Ding; Na He; Shehnaz K. Hussain; Qingwu Jiang; Li-Na Mu; Jianyu Rao; Hua Wang; Nai-Chieh Y. You; et al. (Familial Cancer, 2014)

Reevaluation of the offset of the Great Wall associated with the ca. M 8.0 Pingluo earthquake of 1739, Yinchuan graben, China - Aiming Lin; Gang Rao; Jianmin Hu; Wangbin Gong (Journal of Seismology, 2013)

A new lignan with anti-HBV activity from the roots of Bombax ceiba - Guo Kai Wang; Bin Bin Lin; Rao Rao; Kan Zhu; Xiao Ying Qin; Guo Yong Xie; Min Jian Qin (Natural Product Research, 2013)

Association between polymorphisms in the signal transducer and activator of transcription and dilated cardiomyopathy in the Chinese Han population - Ying Peng; Bin Zhou; Yanyun Wang; Yu Chen; Hui Li; Yaping Song; Lin Zhang; Li Rao (Molecular and Cellular Biochemistry, 2012)

Isolation and identification of an acetoin high production bacterium that can reverse transform 2,3-butanediol to acetoin at the decline phase of fermentation - Xian Zhang; Tao-wei Yang; Qing Lin; Mei-juan Xu; Hai-feng Xia; Zheng-hong Xu; Hua-zhong Li; Zhi-ming Rao (World Journal of Microbiology and Biotechnology, 2011)

Distribution of inundation by the great tsunami of the 2011 M w 9.0 earthquake off the Pacific coast of Tohoku (Japan), as revealed by ALOS imagery data - Gang Rao; Aiming Lin (International Journal of Remote Sensing, 2011)

Adenosine postconditioning protects against myocardial ischemia–reperfusion injury though modulate production of TNF-α and prevents activation of transcription factor NF-kappaB - Jian-Juan Ke; Feng-Xu Yu; Yan Rao; Yan-Lin Wang (Molecular Biology Reports, 2011)

A multiple-dose pharmacokinetics of polyethylene glycol recombinant human interleukin-6 (PEG-rhIL-6) in rats - Xue-ling He; Hai-lin Yin; Jiang Wu; Ke Zhang; Yan Liu; Tao Yuan; Hai-lin Rao; Liang Li; Guang Yang; Xue-mei Zhang (Journal of Zhejiang University-SCIENCE B, 2011)

A New Phosphorimetry for the Determination of Trace Alkaline Phosphatase Using Multi-wall Carbon Nanotubes and Its Diagnosis of Human Diseases - Jia-Ming Liu; Ying Rao; Li Chen; Xin-Xing Wang; Li-Ping Lin; Chang-Qing Lin; Li-Hong Zhang; Ying Ou-Yang (Journal of Fluorescence, 2010)

Impact of GPS radio occultation data assimilation on regional weather predictions - Ching-Yuang Huang; Ying-Hwa Kuo; Shu-Ya Chen; Chuen-Tsyr Terng; Fang-Ching Chien; Pay-Liam Lin; Mien-Tze Kueh; Shu-Hua Chen; Ming-Jen Yang; Chieh-Ju Wang; Anisetty S. K. A. V. Prasad Rao (GPS Solutions, 2010)

Detection of survivin-expressing circulating cancer cells in the peripheral blood of patients with esophageal squamous cell carcinoma and its clinical significance - Mei Cao; Shang-Mian Yie; Sheng-Min Wu; Shu Chen; Be Lou; Xu He; Shang-Rong Ye; Ke Xie; Lin Rao; En Gao; Nai-Yao Ye (Clinical & Experimental Metastasis, 2009)

Expression and production of bioactive human interleukin-18 in transgenic tobacco plants - Bin Zhang; Ying-Hua Yang; Yong-Ming Lin; Qing Rao; Guo-Guang Zheng; Ke-Fu Wu (Biotechnology Letters, 2003)

Effect of bupropion-SR on REM sleep: relationship to antidepressant response - Geoffrey Ott; Uma Rao; Innocencia Nuccio; Keh-Ming Lin; Russell Poland (Psychopharmacology, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

The effect of agricultural practices on methane and nitrous oxide emissions from rice field and pot experiments - Li Yue; Lin Erda; Rao Minjie (Nutrient Cycling in Agroecosystems, 1997)